2016
DOI: 10.5130/ajceb.v16i2.4741
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the beliefs of Australian prefabricated house builders

Abstract: The housing sector accounts for a majority of newly constructed buildings. Prefabrication, defined as the factory construction of houses or significant components, is widely promoted as a means to improve efficiency. This paper focuses on the research questions: RQ1. What are the attitudes of builders towards prefabrication adoption? RQ2. What types of stakeholders do builders believe influence their adoption decisions? RQ3. What types of contextual influences do builders believe impact their adoption decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…However, it seems that stakeholders tend to simplify the decision-making process in the selection of OSM as a construction method. Industry evidence indicates that stakeholders' decision of OSM use largely relies on their historical experience or the cost-related performance (Chen et al 2010;Park et al 2011;Steinhardt and Manley 2016). For instance, Steinhardt and Manley (2016) revealed that the builders' determination relies on their attitudes, beliefs, and autonomy.…”
Section: Stakeholders' Selection Criteria Of Osm As a Construction Mementioning
confidence: 99%
See 3 more Smart Citations
“…However, it seems that stakeholders tend to simplify the decision-making process in the selection of OSM as a construction method. Industry evidence indicates that stakeholders' decision of OSM use largely relies on their historical experience or the cost-related performance (Chen et al 2010;Park et al 2011;Steinhardt and Manley 2016). For instance, Steinhardt and Manley (2016) revealed that the builders' determination relies on their attitudes, beliefs, and autonomy.…”
Section: Stakeholders' Selection Criteria Of Osm As a Construction Mementioning
confidence: 99%
“…Industry evidence indicates that stakeholders' decision of OSM use largely relies on their historical experience or the cost-related performance (Chen et al 2010;Park et al 2011;Steinhardt and Manley 2016). For instance, Steinhardt and Manley (2016) revealed that the builders' determination relies on their attitudes, beliefs, and autonomy. However, this leads to poor implementation or project failure as the decisionmaking process is complicated with the need of assessing various factors such as industry-related and firm-related ones (Zakaria et al 2018;Azhar et al 2013;Gibb and Neale 1997;Noorzai et al 2017; This material may be downloaded for personal use only.…”
Section: Stakeholders' Selection Criteria Of Osm As a Construction Mementioning
confidence: 99%
See 2 more Smart Citations
“…Contrastingly, the prefab or modular-build, particularly in Anglophone Western countries, is more commonly understood as a failed architectural experiment (Aitchison and Macarthur, 2017). However, in large part due to austerity conditions restricting funding for house-building, modular construction is once again becoming more commonplace (Steinhardt and Manley, 2016).…”
Section: "We Start To Panic" Bringing Home Collective Anxieties Aftementioning
confidence: 99%